Networked learning and problem and project based learning – how they complement each other - Dirckinck-Holmfeld, Lone (Proceedings of the International Conference on Networked Learning, 2016)
Networked learning is both a pedagogy and a philosophy, and so is problem and project-based learning. Both approaches have been greatly influenced by the traditions of open learning and other radical pedagogies and humanistic educational ideas of Dewey, Freire, Giroux, Rogers, Negt and others. However, despite similarities in their educational ideas and pedagogies, the two approaches differ considerably. From the beginning, networked learning has focused on the integration of information and communication technologies as well as the promotion of connections – between learners, between learners and tutors and between the learning community and learning resources. On the other hand, problem and project-based learning has been characterised by a number of combined pedagogical principles: problem formulation and enquiry of exemplary problems (anomalies), participant control, interdisciplinarity, joint collaborative projects and action learning stressing the interdependencies among learners and their engagement in the research of ill-structured and open societal problems. Building on Nicolajsen and Ryberg (2014) and Tambouris et al. (2012), the overall changes and potential in the educational digital landscape and in NL can be summarised as follows: (1) a move from hierarchical structures based on courses and topics toward more student-centred networks; (2) a change from dissemination toward horizontal patterns of knowledge exchange and peer learning; (3) a change from learning management systems (LMSs) toward personal learning environments (PLEs); (4) a move toward encouraging exchange, sharing and students’ production of knowledge and artefacts; and (5) a shift from classical curriculum toward 21st-century skills and networked digital scholarship. Within this landscape of change, the paper discusses the core principles of networked learning and problem based learning design, respectively, addressing the ethical claim of dialogue as an I-You relation, omnipresent digital technologies and social media as connecting the learner, Castells’ concept of “space of flows” as the material arrangements of simultaneity of social practices without territorial contiguity, personal learning environments, and the positive means of interdependencies in project work. The aim of this paper is to examine the two approaches and discuss on a conceptual level how they may complement each other in the endeavour to further develop a critical pedagogy while still providing guiding principles for a practical approach to university teaching and learning.